Health Implications of Physical Activity Participation of Second Cycle School Students (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
The general objective of the study is to investigate health implications of physical activity participation of second cycle school students in Kumasi, Ashanti region of Ghana. This exploratory research recruited 660 SHS students (mean aged=16.51 Â± 18.41 years). Age, height, weight, waist to hip ratio, BMI, systolic and diastolic blood pressure and resting energy expenditure were measured. Physical activity involvements were identified using modified SQUASH questionnaire. The prevalence of sedentary lifestyle due to the introduction of modern technological implements in learning, recreation and occupation play significant roles among the causes of cardiovascular risk factors globally. In Ghana, senior high school (SHS) students partake in physical activity (PA) as part of their physical education programme but there is scarce information on the health implications of such participation. This study examined the health implications of PA participation of senior high school students in Kumasi with emphasis on gender, weight, BMI, heart rate, waist to hip ratio and blood pressure. This study concluded that second cycle school students are physically active with incidences of overweight, obesity and morbidity. The PA program and time spent by those overweight, obese and morbid should be re-designed to prevent cardiovascular risk factors.